Error Analysis of Using Simple Present Tense in 8th Graders’ Descriptive Text - Putri Fauziah (ETNOLINGUAL, 2022)
Abstract Simple Present Tense is element of grammar that said in tenses. It makes use of to specific day by day activities. Writer ought to use easy gift whilst they'll write approximately their activities. The facts evaluation became six steps through: mistakes detection, finding mistakes, describing mistakes, classifying mistakes, counting mistakes, and placing the end result into table.it became carried out in Junior High School in Sukodono, in particular Eighth Grade. The facts with the aid of using college students Eighth Grade to put in writing descriptive textual content with the aid of using the use of gift traumatic then their works became accumulated and analyzed to get the facts as goal as possible, in order that they may be higher in writing descriptive textual content with the aid of using the use of gift traumatic. After evaluation all textual content, the researcher determined a few locating of the research. Styles of mistakes determined in descriptive textual content in college students writing of the 8th grade of Junior High School in Sukodono, the researcher can discover a few reasons of mistakes. They are interlingual and intralingual switch. Interlingual switch is mistakes which might be inspired with the aid of using the interference of customers‟ mom tongue. The customers nevertheless observe Indonesian sample into English whilst they translate the sentences. Then Intralingual switch takes place whilst college students get problem analyze the second one language. They made mistakes is due to their mom tongue interference and logical questioning and now no longer doing exercise English well. Keywords: Simple Present, Error Analysis, Descriptive text